Self-evaluation by candidate music teachers during individual instrument lesson education (Marmara University case study) - ÇOBAN, SİBEL (ELSEVIER SCIENCE BV, 2011)
This study examined the ideas of music teacher candidates about themselves through self-assessment during individual instrument lessons. The findings indicated that candidate music teachers whose personal instrument was the guitar could play their instruments sufficiently well to succeed in the course. The group who specialized in playing wind instruments expressed the lowest level of agreement with the statement, I play my instrument well enough to be successful in the course (C) 2011 Published by Elsevier Ltd.
Keywords: Occupation Education; Instrument Education; Self-Evaluation; PERFORMANCE